Research on electron paramagnetic resonance of modified phosphate fertilizers - WU Ping-xiao; LIAO Zong-wen (浙江大学学报. 农业与生命科学版)
In the productive process of save sulphuric acid phosphate fertilizer, different proportional additives were added to ground phosphate rock to produce three new modified phosphate fertilizers. The chemical analysis showed that the proportion of water-soluble phosphorus in available phosphorus in the high efficiency phosphate fertilizers had been decreased. Meanwhile the pot experiment showed that three high efficiency phosphate fertilizers had more positive effect on increasing biomass than ordinary superphosphate calcium under the condition of equivalent weight. Moreover, phosphorus uptake by plant and phosphorus content of plant also increased remarkably. We also used Electron paramagnetic resonance (EPR) to analyze the paramagnetic element of modified phosphate fertilizers and corn plant, and found that their EPR spectra peak of modified phosphate fertilizers had been changed greatly than that of phosphate rock. The superfine EPR spectra of Mn2+ in modified phosphate fertilizers disappeared after modified phosphate fertilizers were modified, which meant that the structure of modified phosphate fertilizers had fallen into disorder. Modified phosphate fertilizers could improve balanced absorption of Fe3+ and Mn2+, which was responsible for the biomass production increase.